(untitled) (Marketing Journal, 2025)
Programmatic advertising has transformed the digital marketing landscape by enabling automated, data -driven ad purchasing and optimization. This study examines the integration of programmatic advertising in the tourism sector, emphasizing its role in enhancing targeted marketing strategies and optimizing advertising budgets. Through an in -depth analysis of current industry trends, technological advancements, and empirical evidence, the study de monstrates the effectiveness of programmatic advertising in boosting consumer engagement and improving return on investment (ROI) for tourism businesses. Additionally, it addresses key challenges such as data privacy concerns and technological limitations while offering strategic recommendations for enhancing programmatic advertising initiatives in the tourism industry.